2017
DOI: 10.58397/ashkmdc.v22i1.93
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction from Dental Services Provided by Multan Medical & Dental College

Abstract: Objective: The aim of this study was to assess the level and factors influencing the level of patient satisfaction from dental services provided by Multan Dental Hospital. Methods: Study was carried out at Multan Dental hospital from 1st June to 30th July 2015. Total  256 patients over 18 years of age, participated  in  this  cross-sectional  study.  Convenient  sampling  tech- nique was used to  select  the  patients.  The  Hogan  Patient  Satisfaction  Questionnaire  was   customised, personalised and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…This tendency is also reported in the studies [ 23 , 35 ]. In contrast, other studies [ 6 , 9 , 33 , 36 , 37 ] revealed that patients with higher education reported lower levels of satisfaction with dental services, possibly due to a higher expectation level. In the study of Amorim [ 29 ], patients with a lower level of education show a higher degree of satisfaction, an aspect that they do not consider relevant due to the fact that a lower level of education can create a false opinion of patients regarding the quality of the medical services they have benefited from.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…This tendency is also reported in the studies [ 23 , 35 ]. In contrast, other studies [ 6 , 9 , 33 , 36 , 37 ] revealed that patients with higher education reported lower levels of satisfaction with dental services, possibly due to a higher expectation level. In the study of Amorim [ 29 ], patients with a lower level of education show a higher degree of satisfaction, an aspect that they do not consider relevant due to the fact that a lower level of education can create a false opinion of patients regarding the quality of the medical services they have benefited from.…”
Section: Discussionmentioning
confidence: 76%
“…Lower satisfaction among men (in comparison with women) regarding accessibility, reception area and reception staff was also reported in Hussein’s study [ 6 ], with results that were similar to our findings. In contrast, there are studies [ 33 , 34 ] reporting a higher degree of satisfaction among men, an aspect attributed to possible higher expectations of medical services among women.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…1 Patients' satisfaction with health services is considered an essential element for hospital/clinical setup as it measures the hospital's performance and its quality of care (which is an amalgamation of patient satisfaction and treatment outcome). [2][3][4] Evaluation of patients' satisfaction has become a basic concern of clinical practice 5 because satisfied patients are more likely to show positive illness behaviors. 6 Response to satisfaction with dental care is fundamental for continuous improvement of the service delivery process and outcome 7 because the satisfaction of the patient with the services can be measured in terms of access, convenience, cost, pain, and quality.…”
Section: Introductionmentioning
confidence: 99%
“…Satisfaction is the extent to which an individual's experience compares with his or her expectations 1 . Patients' satisfaction with health services is considered an essential element for hospital/clinical setup as it measures the hospital's performance and its quality of care (which is an amalgamation of patient satisfaction and treatment outcome) 2–4 …”
Section: Introductionmentioning
confidence: 99%